Biomonitoring of Mimachlamys varia transplanted to areas impacted by human activities (La Rochelle Marina, France). (March 2020) - Breitwieser, Marine; Barbarin, Marine; Plumejeaud-Perreau, Christine; Dubillot, Emmanuel; Guyot, Thierry; Huet, Valérie; Churlaud, Carine; Coulombier, Thibaut; Brenon, Isabelle; Fichet, Denis; Imbert, Nathalie; Thomas, Hélène
Abstract: The development of human activities on French Atlantic coastlines (La Rochelle) lead to chronic pollution of the environment by organic (pesticides, hydrocarbons, agrochemicals) and inorganic (heavy metals) contaminants. These past years, several regulations have been implemented to preserve coastal environments. The purpose of this study was to perform biomonitoring of bivalve species using an outdoor caging technique. The goal of our work was to assess the impact of harbour's trace elements on the state of health of the marine bivalve Mimachlamys varia. First, various molecular defence biomarkers were measured: SOD (oxidative stress), GST (detoxification process), MDA (lipid peroxidation), and Laccase (immune reaction). Thus, in April 2016, scallops were collected at three caging sites, which differ by their levels of pollution, after transplantation into port areas (fairing, rainwater) and a control site (marsh). Bivalve samples were taken at three sampling dates (D0, D07, D21). Biomarker assays were performed in the digestive glands due to their bioaccumulation properties. The second aim was to explore the impacts of inorganic pollutants placed in environmental harbour's sites. After 21 days, the biomarker response of transplanted bivalves revealed a SOD decrease, Laccase and GST stimulations, higher concentrations in Cu, Fe, As, Co, Mn, Zn, Sn and no significant variation of MDA concentration. Our ecological relevance of biomarker approaches opens interesting perspectives to identify M. varia such as a pertinent marine sentinel species. The several selected biomarkers determined could confirm their ability to appraise the water quality of hydro-systems located in French coastlines, such as port areas. Highlights: Biomonitoring study was carried out along in two La Rochelle port areas (fairing and rainwaters) using  M. varia  species. Biomarker responses was evaluated in the digestive gland organ. Chronic exposure induced biotransformation, antioxidants and immune modulation in variegated scallops. Several selected biomarkers confirmed their ability to assess the water quality of hydro-systems, including port areas.